Cane Hay Cost-Return Budget in Western Kansas - Dumler, Troy J.; Thompson, Curtis R. (My University, 2004)
This publication estimates the costs and returns associated with a typical sorghum sudangrass hybrid planted at heavier seeding rates and harvested as a hay crop in western Kansas.
MF997_2004_10
Keywords: MF997; Economics; Crops; MF